A Low-Cost Humidity Control System to Protect Microscopes in a Tropical Climate - Anders J. Asp; Christina M. Webber; Evan N. Nicolai; Gabriel Martínez-Gálvez; Victoria S. Marks; Ephraim I. Ben-Abraham; John W. Willson; J. Luis Luján (Ubiquity Press, 2020)
Introduction: A clean and functional microscope is necessary for accurate diagnosis of infectious diseases. In tropical climates, high humidity levels and improper storage conditions allow for the accumulation of debris and fungus on the optical components of diagnostic equipment, such as microscopes. Objective: Our objective was to develop and implement a low-cost, sustainable, easy to manage, low-maintenance, passive humidity control chamber to both reduce debris accumulation and microbial growth onto the optical components of microscopes. Methods: Constructed from easily-sourced and locally available materials, the cost of each humidity control chamber is approximately $2.35 USD. Relative humidity levels were recorded every 30 minutes over a period of 10 weeks from two chambers deployed at the Belize Vector and Ecology Center and the University of Belize. Results: The humidity control chamber deployed at the University of Belize maintained internal relative humidity at an average of 35.3% (SD = 4.2%) over 10 weeks, while the average external relative humidity was 86.4% (SD = 12.4%). The humidity control chamber deployed at the Belize Vector and Ecology Center effectively maintained internal relative humidity to an average of 54.5% (SD = 9.4%) over 10 weeks, while the average external relative humidity was 86.9% (SD = 12.9%). Conclusions: Control of relative humidity is paramount for the sustainability of medical equipment in tropical climates. The humidity control chambers reduced relative humidity to levels that were not conducive for fungal growth while reducing microscope contamination from external sources. This will likely extend the service life of the microscopes while taking advantage of low-cost, locally sourced components.